Synergy between Journalists and PR Agencies Hasta Communications to Obtain Client Satisfaction - Erlita Zahrah; Wahyunengsih Wahyunengsih (Lembaga Pengembangan Kinerja Dosen, 2023)
This research focuses on the role of journalists in news dissemination. It aims to provide clear information about the environment itself. Then the role of media relations cannot be separated from broad communication tasks, for journalists/press to participate or establish large relationships by an organization or company, which will later affect the delivery of messages in communication. Therefore, good relations are needed between public relations experts and journalists so that the messages conveyed by PR are channeled to the media so that they reach the wider community. The method used in this study is the method of observation and interviews with a qualitative approach. Observation and interview methods complement each other, the presentation of information obtained from various media is a combination of various information materials extracted from observations and interviews so that each collection technique does not stand alone.